Joint Prediction Bands for Macroeconomic Risk Management - Q. Farooq Akram; Andrew Binning; Junior Maih (Norges Bank, 2016)
In this paper we address the issue of assessing and communicating the joint probabilities implied by density forecasts from multivariate time series models. We focus our attention in three areas. First, we investigate a new method of producing fan charts that better communicates the uncertainty present in forecasts from multivariate time series models. Second, we suggest a new measure for assessing the plausibility of non-central point forecasts. And third, we describe how to use the density forecasts from a multivariate time series model to assess the probability of a set of future events occurring. An additional novelty of this paper is our use of a regime-switching DSGE model with an occasionally binding zero lower bound constraint, estimated on US data, to produce the density forecasts. The tools we off er will allow practitioners to better assess and communicate joint forecast probabilities, a criticism that has been leveled at central bank communications.
hdl:11250/2495725
Keywords: C6; C11; C53; E1; E5; E37; 330; DSGE; Bayesian estimation; monetary policy; fan charts; zero lower bound; regime-switching